Anxiety, sleep quality and stress in college students during the COVID-19 confinement (2022)
Confinement by COVID-19 impacted the physical, mental and psychological health of the Colombian population and other countries, increasing the rates of stress, anxiety, and insomnia, which is an alert to mental health professionals. Therefore, this article aims to analyze the impact of confinement due to COVID-19 on the quality of sleep, anxiety, and stress in young people, with the main objective of observing the relevant changes perceived in the population as well as significant aspects in mental health that may affect the population, through a review of the literature associated with the problem posed and analysis of variables in them, from different scientific sources.